Zoology and Animal Ecology: Abstract book : 31 January 2024, Nature House University of Latvia, Riga, Latvia - 82nd International Scientific Conference of the University of Latvia; University of Latvia, Faculty of Biology (Latvijas Universitāte, 2024)
The Zoology and Animal Ecology section of the conference covers a broad range of topics, ranging from the distribution of animal species and the different aspects of species' interactions with the environment to animal genetics and physiology, including behaviour, conservation and other topics where study objects are animals.
Zooloģija un dzīvnieku ekoloģija : Latvijas Universitātes 82. zinātniskā konference, Bioloģijas sekcija : Referātu tēzu krājums
Keywords: Veterinary epidemiology; Molecular biology; Morphology; Systematics and phylogenetics; Terrestrial ecology; Ethology and behavioural ecology; Research Subject Categories::NATURAL SCIENCES::Biology::Terrestrial, freshwater and marine ecology; Research Subject Categories::NATURAL SCIENCES::Biology::Organism biology